Determination of sex dimorphisms of the thickness of the hard palate in adolescence using computed tomography: Pilot study - Aleshkina, Olga; Suetenkov, Dmitriy; Dydykin, Sergey; Vasil'ev, Yuriy; Paulsen, Friedrich; Firsova, Irina; Bikbaeva, Tatiana; Polkovova, Irina (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Background: In addition to traditional craniometric techniques, computer craniometry has been used in recent decades, including stereometric methods, which make it possible to determine the microanatomical spatial relationships and dimensional features of various structures of the skull, in particular the thickness of the inert palate of the maxilla. Aim: Determination of the gender-specific variability of the thickness of the bony palate at the age of 18–20 years using CT. Material and methods: The material of the pilot study were 40 computed tomograms of young males and females aged 18–20 years. The method of computer craniometry was used to measure the thickness of the bony palate in sagittal projection taking into account the gender. A graphic raster map was created to identify the palatal areas, then analyze their thickness and determine the safe zones for the mini dental implants. Results: In young males and females (18–20 years) the thickness of the bony palate decreases at different levels from front to back and from the median suture to the alveolar process. The greatest thickness of the bony palate corresponds to its anterior third and reliably predominates in young males at all levels compared to young females. In the middle and posterior third palate, the averages do not show gender differences and their variation is insignificant. Conclusions: The greatest thickness of the bony palate can be used as the most favorable zone for the fixation of orthodontic mini dental implants. The variability in the thickness of the bony palate should be considered when selecting the most optimal zones and depth of mini-implant placement.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Adolescence; Bone palate; Mini dental implants; Orthodontic mini-screws